Late payments on mortgage loans and unemployment: Evidence from a German household panel - Axel Möhlmann; Edgar Vogel (Deutsche Bundesbank, 2024)
This paper empirically analyses the effect of unemployment on mortgage loan late payments using German household panel data. Regressions with individual fixed effects suggest that for each person who becomes unemployed, the probability of missing a mortgage payment increases by two percentage points. The effect intensifies with the length of unemployment. When examining the interaction between mortgage late payments and households' debt service, we find that higher borrower-based risk amplifies the effect of unemployment. Crucially, the effect is non-linear. The odds of individuals who have lost their jobs making a late mortgage payment increases disproportionately for those with a debt service ratio of 30% to 40% of their income. This implies that capping debt service to income ratios can reduce the risk of mortgage defaults and buffer against labour market shocks, which is relevant for financial stability analysis and macroprudential regulation.
Keywords: D14; G28; G21; G33; G51; J63; L85; 330; Mortgage loans; default; unemployment; DSTI; macroprudential policy; financial stability